THE STRUCTURAL AND MICROSTRUCTURAL characteristics IN THE MILLED Fe50C50 MAGNETIC COMPOSITES - Setyo Purwanto; Engkir Sukirman (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2007)
THE STRUCTURAL AND MICROSTRUCTURAL characteristics IN THE MILLED Fe50C50 MAGNETIC COMPOSITES. The structural and microstructural characteristics in the milled Fe50C50 magnetic composites have been investigated by the x-ray diffraction technique using Rietveld analysis method. The starting materials of composite were the pure iron (Fe) and carbon (C) powders (weight ratio Fe:C = 50:50). The composites were prepared by mixing Fe and C powders by high energy milling (HEM) at various milling time start from 1.5 to 4.5 h. The x-rays diffraction measurements were performed by using a Philips X-Ray Diffractometer, PW170 type at room temperature with CuKα radiation, 2θ range = 10°-100°, preset time = 1 sec, and step size = 0.020°. With a mechanical milling of 4.5 hours, the elemental powders undergo a better crystallization. It means that the amorphization. Of its components do not happen yet. The carbon elements in composites get a homogeneous strain field, while the iron elements get an inhomogeneous strain field. The crystallite size of C particles almost do not change yet until the milling time of 4.5 hours. This is presumably due to the C particles are trapped at the weld interfaces between the Fe particles. While, the Fe particles fracture into smaller segments on the milling time of 1.5 hours. On the further milling, the Fe particles undergo welding processes to be bigger crystallites. Magnetic parameter such as Hc, Ms and Ku were confirmed this suggestion.